2015
DOI: 10.1371/journal.pone.0142983
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Practice Experiences in Diagnosis and Treatment of Traumatic Brain Injury in Children: A Survey among Clinicians at 9 Large Hospitals in China

Abstract: Proper diagnosis and treatment of traumatic brain injury (TBI) in children is becoming an increasingly problematic issue in China. This study investigated Chinese clinicians to provide information about their knowledge and experiences in diagnosis and treatment of pediatric TBI. We conducted a questionnaire survey among clinicians in the emergency departments and neurosurgery departments at 9 major hospitals in China. The questionnaire included demographic information, and knowledge and experiences regarding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…Unfortunately, in a survey among nine large hospitals in China, 80% of clinicians reported that there was no treatment guideline for pediatric TBI in China, 91.9% reported that CT scans were routinely performed in all suspected patients. [ 29 ] In regard to acute head CT use for conscious children, our finding might be helpful in clinical decision-making practices. CHALICE, PECARN, and CATCH are commonly used clinical decision rules, guiding CT use for children patients with mild TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, in a survey among nine large hospitals in China, 80% of clinicians reported that there was no treatment guideline for pediatric TBI in China, 91.9% reported that CT scans were routinely performed in all suspected patients. [ 29 ] In regard to acute head CT use for conscious children, our finding might be helpful in clinical decision-making practices. CHALICE, PECARN, and CATCH are commonly used clinical decision rules, guiding CT use for children patients with mild TBI.…”
Section: Discussionmentioning
confidence: 99%
“…Children with mild TBI (mTBI)—those with Glasgow Coma Scale (GCS) scores of 13 to 15—comprise the most common TBI subgroup, constituting more than 90% of new pediatric TBI cases and approximately one-third of the 50 000 to 60 000 TBI hospitalizations each year . Despite the prevalence and potentially significant harms affecting children with mTBI, there is significant variability and often uncertainty in the treatment of these patients …”
Section: Introductionmentioning
confidence: 99%
“…5 Despite the prevalence and potentially significant harms affecting children with mTBI, there is significant variability and often uncertainty in the treatment of these patients. 6,7 In 2009, the Pediatric Emergency Care Applied Research Network (PECARN) derived and validated clinical decision tools for identifying which children with minor head injuries are at risk for clinically important TBI. 8 While this study helped identify which children with minor head injuries should receive computed tomographic (CT) imaging, among those with intracranial injury (ICI) identified on CT, there is limited evidence guiding appropriate care pathways.…”
mentioning
confidence: 99%
“…There is, in general, nonavailability of on the spot resuscitation facility, poorly organized, equipped transport of patient and emergency services; lack of team approach the developing world like India. [ 4 ]…”
Section: Introductionmentioning
confidence: 99%